Research progress analysis on risk assessment of runway excursion - ZHAO Dingyi; QI Xinge; WANG Lei (Hangkong gongcheng jinzhan)
Runway excursion ranks second among the most catastrophic symptoms. Research on the risk assessment of runway excursion has been done by domestic and international civil aviation research institutes，specialists，and academics in an effort to lessen both its likelihood and its effects. Several important contributing variables have been the subject of recent study，including unfavorable weather circumstances，runway surface conditions，pilot mistakes，and mechanical issues. These issues can be resolved by improving runway maintenance and improving pilot training. In this paper，the accomplishments and flaws are compiled by looking at the current designs of both domestic and international experts on the runway excursion occurrences. The techniques for predicting and analyzing the danger of a runway excursion are described，and suggestions for more research are made for future study.